2021
DOI: 10.1016/j.tem.2020.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Confection Confusion: Interplay Between Diet, Taste, and Nutrition

Abstract: Although genetics shapes our sense of taste to prefer some foods over others, taste sensation is plastic and changes with age, disease state, and nutrition. We have known for decades that diet composition can influence the way we perceive foods, but many questions remain unanswered, particularly regarding the effects of chemosensory plasticity on feeding behavior. Here, we review recent evidence on the effects of high-nutrient diets, especially high dietary sugar, on sweet taste in vinegar flies, rodents, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 100 publications
0
30
0
Order By: Relevance
“…By contrast, the CAF and CAF-R fed rats already had daily sweet food experience from muffins, biscuits, and sugared jelly milk components of the cafeteria diet from a young age. Evidence from different animal models suggests that sensitivity and intensity of taste sensations changes with diet composition, thus involving a diet-dependent chemosensory plasticity that would result in changes to taste perceptions, their elicited responses and diet-related behavior (see May and Dus 2021 [7]). Evidence of dopamine (DA) neurotransmission changes associated with sugar consumption in sweetnaïve rats comes from Hajnal and Norgren 2001 [43] who, using microdialysis, reported that rats licking a 0.3 M sucrose solution showed a 305% increase in extracellular levels of DA and monoamine metabolites in the nucleus accumbens (NAcc) compared with water intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the CAF and CAF-R fed rats already had daily sweet food experience from muffins, biscuits, and sugared jelly milk components of the cafeteria diet from a young age. Evidence from different animal models suggests that sensitivity and intensity of taste sensations changes with diet composition, thus involving a diet-dependent chemosensory plasticity that would result in changes to taste perceptions, their elicited responses and diet-related behavior (see May and Dus 2021 [7]). Evidence of dopamine (DA) neurotransmission changes associated with sugar consumption in sweetnaïve rats comes from Hajnal and Norgren 2001 [43] who, using microdialysis, reported that rats licking a 0.3 M sucrose solution showed a 305% increase in extracellular levels of DA and monoamine metabolites in the nucleus accumbens (NAcc) compared with water intake.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether these changes are associated with the metabolic consequences of obesity or are the consequence of the sucrose consumption per se remain unclear [6]. The possibility that the taste system can increase or decrease its sensitivity with diet composition and influence food preference, choice, and overall energy intake, through diet-dependent chemosensory mechanisms of plasticity has been proposed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the main factor contributing to the development of obesity has been overeating [1]. The preference for palatable, high-calorie food induces overeating and contributes to the epidemic prevalence of obesity [2,3]. In this regard, it is of particular interest to search for drugs that not only correct metabolic disorders associated with obesity but also shift taste preferences toward food products with a balanced composition of macronutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, one of the main causes of the widespread occurrence of obesity and conditions associated therewith is the consumption of high-calorie food (Astrup et al, 2008). The choice of food considerably depends on taste preferences (Duffy et al, 2009), and the preference to palatable fatty and sweet (obesogenic) food contributes to the epidemic prevalence of obesity (May, Dus, 2021;Spinelli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%